HIV-1 Nef-associated Factor 1 Enhances Viral Production by Interacting with CRM1 to Promote Nuclear Export of Unspliced HIV-1 gag mRNA - Ren, Xiao-Xin (J Biol Chem, 2016)
HIV-1 depends on host-cell-encoded factors to complete its life cycle. A comprehensive understanding of how HIV-1 manipulates host machineries during viral infection can facilitate the identification of host targets for antiviral drugs or gene therapy. The cellular protein Naf1 (HIV-1 Nef-associated factor 1) is a CRM1-dependent nucleo-cytoplasmic shuttling protein, and has been identified to regulate multiple receptor-mediated signal pathways in inflammation. The cytoplasm-located Naf1 can inhibit NF-κB activation through binding to A20, and the loss of Naf1 controlled NF-κB activation is associated with multiple autoimmune diseases. However, the effect of Naf1 on HIV-1 mRNA expression has not been characterized. In this study we found that the nucleus-located Naf1 could promote nuclear export of unspliced HIV-1 gag mRNA. We demonstrated that the association between Naf1 and CRM1 was required for this function as the inhibition or knockdown of CRM1 expression significantly impaired Naf1-promoted HIV-1 production. The mutation of Naf1 nuclear export signals (NESs) that account for CRM1 recruitment for nuclear export decreased Naf1 function. Additionally, the mutation of the nuclear localization signal (NLS) of Naf1 diminished its ability to promote HIV-1 production, demonstrating that the shuttling property of Naf1 is required for this function. Our results reveal a novel role of Naf1 in enhancing HIV-1 production, and provide a potential therapeutic target for controlling HIV-1 infection.